PADRÕES ESPACIAIS DA MOBILIDADE DE TRABALHADORES QUALIFICADOS NAS REGIÕES BRASILEIRAS (Gestão & Regionalidade, 2024)
The mobility of skilled workers represents an important way of knowledge spillovers as it has the capacity to increase the generation and diffusion of new knowledge on the regions. In this regard, the objective of this article is to present the patterns of spatial mobility of skilled workers in Brazilian regions. The patterns of the mobility of workers between microregions across the country was constructed with microdata from the Ministry of Labor for the period 2009-2014. This article contributes to the debate on the Brazilian regional dynamics. The results show that the Metropolitan Region of São Paulo, some capital and medium-sized Brazilian cities were the regions that received more qualified workers, with the highlight on the diversified and more technological regions. Also, skilled workers move perceptually more than the total number of workers.